Rejoinder to Guenzl on Theft and the Return of Private Property - Block, Walter E. (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Suppose A is the rightful owner of some property, B steals if from him, and C, in turn, relieves B of his ill-gotten gains. What next? Under just law, must C return the item to A? If not, is C guilty of a crime? If C does return this resource to its initial (rightful?) owner, does A owe C a percentage of its value, as under salvage law? These are some of the questions to be wrestled with in the present paper
Keywords: własność; agresja; kradzież; libertarianizm